SUPLEMENTASI EKSTRAK RUMPUT LAUT KAPPAPHYCUS ALVAREZII DAN EUCHEUMA DENTICULATUM UNTUK MENINGKATKAN PERTUMBUHAN DAN RESPON IMUN LITOPENAEUS VANNAMEI TERHADAP VIBRIO HARVEYI - Fitri Nurjannah, Nisrina
One of the most common diseases found in cultured shrimp is vibriosis, one of which is caused by Vibrio harveyi. Supplementation of seaweed extracts Kappaphycus alvarezii and Eucheuma denticulatum separately in feed has the potential to increase shrimp resistance to vibriosis. This study was aimed to determine the optimum concentration variation of seaweed extract supplementation of K. alvarezii and E. denticulatum in increasing growth, immune response, and survival of Litopenaeus vannamei shrimp after being challenged with V. harveyi. In this study, four variations of seaweed extract supplements were used, namely ABD1 2.5 g/kg and ABD3 1 g/kg which were made from K. alvarezii, ABD5-1x 3 gr/kg and ABD5-1x 6 gr/kg which were made from E. denticulatum,and compared with controls without the addition of supplements. The feeding trial with the use of supplements was carried out for 14 days at an initial culture density of 65 individuals/L. Subsequently, a challenge test was carried out with the addition of V. harveyi at a concentration of 106 CFU/ml and shrimp rearing for 7 days of culture period. Biological parameter analysis was performed at the end of the challenge test and analysis of immune-related genes expression (lectin, pen2, pen3, crustin, alf-A, lysozyme, and proPO) was performed on day 1, 3, and 7 of the challenge test periods using qPCR method. Analysis of biological parameters showed that ABD3 1 g/kg gave the best results on feed conversion ratio (0.67 ± 0.05), productivity (0.97 ± 0.07 kg/m3), and total biomass (6.76 ± 0.52 grams). This result was significantly higher than other treatments (p<0.05). ABD3 1 g/kg also showed a higher survival rate than the control, which was 78.18 ± 0.06%. Furthermore, supplementation of both K. alvarezii and E. denticulatum extracts was observed to increase the expression of lectin, pen2, crustin, alf-A, and lysozyme genes relative to controls. ABD3 1 gr/kg and ABD5-1x 3 gr/kg variations were able to increase the expression level of immune-related genes better than other variations. ABD3 1 gr/kg showed the highest increase in expression level significantly for pen2, crustin, lysozyme, and alf-A genes on day 1 and 3 (p<0.05), while ABD5-1x 3 gr/kg showed the highest expression of lectin, pen2, and crustin on the day 7. It can be concluded that feed supplementation with K. alvarezii and E. denticulatum extracts was able to increase the growth and survival of L. vannamei after challenge test with Vibrio harveyi, with ABD3 supplementation of K. alvarezii at concentration of 1 g/kg giving the highest increase on both growth and immune-related genes expression. Overall, the use of feed supplementation from K. alvarezii and E. denticulatum can be an alternative strategy for vibriosis biocontrol in superintensive white shrimp culture.